Archaeology of Spiritualities
XVI, 277 p. 42 illus., 29 illus. in color.
Keywords: Archaeology of Spiritualties provides a fresh exploration of the interface between archaeology and religion/spirituality. Archaeological approaches to the study of religion have typically and often unconsciously, drawn on western paradigms, especially Judaeo-Christian (mono)theistic frameworks and academic rationalisations. Archaeologists have rarely reflected on how these approaches have framed and constrained their choices of methodologies, research questions, hypotheses, definitions, interpretations and analyses and have neglected an important dimension of religion: the human experience of the numinous - the power, presence or experience of the supernatural. Within the religions of many of the world’s peoples, sacred experiences – particularly in relation to sacred landscapes and beings connected with those landscapes – are often given greater emphasis, while doctrine and beliefs are relatively less important. Archaeology of Spiritualities asks how such experiences might be discerned in the archaeological record; how do we recognize and investigate ‘other’ forms of religious or spiritual experience in the remains of the past? The volume opens up a space to explore critically and reflexively the encounter between archaeology and diverse cultural expressions of spirituality. It showcases experiential and experimental methodologies in this area of the discipline, an unconventional approach within the archaeology of religion. Thus Archaeology of Spiritualities offers a unique, timely and innovative contribution, one that is also challenging and stimulating. It is a great resource for archaeologists, historians, religious scholars and others interested in cultural and religious heritage.